The Strategic Role of Islamic Education Teachers in Student Counseling - Handrian Cahya Kusuma Maajidu; Nurul Latifatul Inayati (Institut Agama Islam An-Nawawi Purworejo, 2025)
The urgency of implementing Islamic values-based counseling in schools is highly relevant in supporting the overall character development and academic achievement of students. This study aims to examine the role of Islamic Education (PAI) teachers in the implementation of counseling at SMA Negeri 2 Boyolali during the 2023/2024 academic year. A qualitative method with a case study approach was used, involving in-depth interviews, participatory observation, and document analysis to collect data, which was then analyzed thematically. The results of the study indicate that PAI teachers play a strategic role through a structured yet informal approach, collaborating with counseling teachers to provide spiritual, moral, and academic support for students. Challenges such as time constraints, limited facilities, and students' level of openness were identified; however, overall, this counseling guidance was effective in enhancing student participation and trust. These findings enrich understanding of the implementation of religion-based counseling guidance and provide a foundation for developing more optimal counseling services in schools. Further research is recommended to explore more adaptive counseling models by leveraging technology and teacher training.